Himaya nga nabanhaw ug uban pang mga sugilanon - Quijano, Gardeopatra; Cebuano Studies Center (Cebu City USC Press, 2011)
Short stories.
Includes bibliographical references.
Cebuano and English.
Keywords: Cebuano literature; Philipine literature -- Cebuano authors